(3QSGdI aj Yde Gdca MSH QCi GdadGSaI heYdei Gdadc hGdCWHGAs ((3eMeO Hf eMeO Hf CMeO GdUjGO GdeQUai s)
(3ChdgG (B:s
(3HYO GdHSedI GdaUd GdChd ai GdjO GdcHQi (B: (3GYde Cf GdjO GdcHQi JOd ZGdHkG Ydi GdhOGO hGdeMHI GdYGeI hEXgGQ GdCNdGb GdMSfI s
(3BNQgG (B:s
(3heG PcQJ gPg GdCTjGA EdG dJMPQgG hJMPQ CeKGdgG s
(3GdeDda CMO GdQgHGf GdaQfSjScGf Jhai Sf`(B867(3``Is
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B141 s
Keywords: (3GdaQGSIs